Controlling the Chirping of Chorus Waves via Magnetic Field Inhomogeneity. Issue 10 (14th May 2020) - Wu, Yifan; Tao, Xin; Zonca, Fulvio; Chen, Liu; Wang, Shui
Abstract: Whistler mode chorus waves are coherent electromagnetic emissions in planetary magnetospheres, characterized by rising‐tone or falling‐tone chirping elements. Understanding the cause of different chirping directions and their properties is an important step in resolving the long‐standing problem of nonlinear chorus generation. We report here, for the first time, particle‐in‐cell simulations of bidirectional chirping of whistler waves in a uniform magnetic field and falling‐tone‐only chirping in an inhomogeneous field. Combined with previous simulations of rising‐tone‐only emissions, we demonstrate that the background magnetic field inhomogeneity is not required for chirping of chorus, but it plays a key role in determining the chirping direction. The findings of the present work also unveil the critical role of the dipole geometry of Earth's magnetic field in causing the statistical predominance of rising‐tone chorus and the oblique propagation of falling‐tone chorus. Plain Language Summary: Whistler mode chorus is a type of naturally occurring electromagnetic emission in planetary magnetospheres. This important wave is known to produce relativistic electrons in the hazardous radiation belts and to precipitate energetic electrons from space into the upper atmosphere to form diffuse aurora. Chorus consists of discrete spectral elements with fast frequency chirping in either upward (rising‐tone) or downward (falling‐tone) directions. A long‐standing problem is to understand the origin of different chirping directions and their distinctive observational properties. Here, we show, by first‐principle particle simulations, that the background magnetic field inhomogeneity plays a key role in determining the chirping direction and that the dipole geometry of Earth's magnetic field essentially controls the properties of chorus. Our results naturally account for the dominance of rising‐tone chorus and the oblique propagation of falling‐tone chorus and provide important insights into the fundamental mechanism of the nonlinear chirping process. The propagation properties of chorus are also expected to be similar in all planetary magnetospheres with a dipole‐type magnetic field. Key Points: We present the first PIC simulations of falling‐tone chorus waves and chirping with a uniform background magnetic field We demonstrate that the background magnetic field inhomogeneity controls the chirping direction of parallel‐propagating chorus Our results explain the dominance of rising‐tone chorus and the oblique propagation of falling‐tone chorus in the magnetosphere